NEW TIMES, NEW STRATEGIES: PROPOSAL FOR AN ADDITIONAL DIMENSION TO THE 4 P'S FOR E-COMMERCE DOT-COM (Journal of Information Systems and Technology Management, 2015)
Proper marketing management is fundamental to any business endeavor, including dot-coms. However, to date, as identified in a review of the International Journal of Electronic Commerce (IJEC) production and the last 10 years of EnANPAD (EnANPAD is the annual Brazilian Academy of Management conference). There are no works on the applicability of the 4P's to e-commerce, a gap in the literature that this study proposes to fill. It uses a qualitative approach methodology, investigating several empirical studies about digital commerce, and comparing it with the mainstream strategic marketing literature. Inferences were developed, pushing further the theory boundaries of this field. Both the classical works as those from Borden (1964) and Mccarthy (1960) and many other contemporaries are evaluated. The present research utilizes these works as a source of information and data. Using a process of comparison with the marketing mix model, it searches for a possible lack of fit between the related empirical environments and such a model. The results identify several key variables in each of the P's related to security in electronic commerce. This dimension seems to be the key in shaping the perception of customer value, thus supporting its inclusion as a fifth dimension along with the 4P's.